Reactive oxygen species inhibit catalytic activity of peptidylarginine deiminase - Dres Damgaard; Mads Emil Bjørn; Peter Østrup Jensen; Claus Henrik Nielsen (Taylor & Francis Group, 2017)
Protein citrullination catalysed by peptidylarginine deiminase (PAD) may play an important pathogenic role in several chronic inflammatory diseases and malignancies. PAD2, PAD4, and citrullinated proteins are found in the synovium of rheumatoid arthritis patients. PAD activity is dependent on calcium and reducing conditions. However, reactive oxygen species (ROS) have been shown to induce citrullination of histones in granulocytes. Here we examine the ability of H2O2 and leukocyte-derived ROS to regulate PAD activity using citrullination of fibrinogen as read-out. H2O2 at concentrations above 40 µM inhibited the catalytic activity of PAD2 and PAD4 in a dose-dependent manner. PMA-stimulated leukocytes citrullinated fibrinogen and this citrullination was markedly enhanced when ROS formation was inhibited by the NADPH oxidase inhibitor diphenyleneiodonium (DPI). In contrast, PAD released from stimulated leukocytes was unaffected by exogenously added H2O2 at concentrations up to 1000 µM. The role of ROS in regulating PAD activity may play an important part in preventing hypercitrullination of proteins.